Bandwidth Widening Strategies for Piezoelectric Based Energy Harvesting from Ambient Vibration Sources - Kok, Swee Leong; Ab Rahman, Mohd Fauzi; Yap, David F. W.; Ho, Yih Hwa (2011)
Due to the fact that the ambient vibration sources are random and unpredictable, therefore a vibration based energy harvesting device is desirable to be able to operate at wider bandwidth in an envelop of frequency range to generate maximum electrical output. In this paper, various ambient vibration from household appliances, machineries, vehicle and moving vehicle were measured and investigated. The second part of the paper will discuss the strategies to harvest these ambient vibration sources. An array of piezoelectric multi-cantilever is proposed to address the issue of single piezoelectric cantilever with high Q-factor. Two configurations of multi-cantilever were fabricated in a form that elevated from the substrate as freestanding structures. One with six cantilevers of constant width but different lengths and another with five cantilevers of constant length but different widths. The measurement and experimental results show a frequency band of 200 Hz to 300 Hz as a common bandwith between the vibration sources and the capability of miniature piezoelectric energy harvester in harvesting maximum electrical energy.